AB1269 REGIONAL DIFFERENCES IN THE PATIENTS' UNDERSTANDING OF TREATMENT STRATEGY IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Cobilinschi, C.; Danila, M.; Opris-Belinski, D.; Saulescu, I.; Groseanu, L.; Daia-Iliescu, S.; Codreanu, C.; Ionescu, R.; Parvu, M.; Popoviciu, H.; Ancuta, C.; Rezus, E.; et al.
Abstract : Background: The treat-to target (T2T) concept is the standard for treating rheumatoid arthritis (RA) patients worldwide 1 . However, difficulties that patients encounter in achieving disease control may differ between regions, which may impact the type of support needed for successful T2T implementation. Objectives: To compare differences in patient-reported challenges to controlling RA-related issues between Romanian and US patients. Methods: A cross-sectional study that recruited 403 RA patients was conducted in six centers in Romania. Patients were invited to complete an RA-related questionnaire. We compared their responses to those from a previous published study that included patients with RA from the US 2 . The survey included items on subjective beliefs about RA treatment (e.g. adherence, cost, adverse events) and knowledge about T2T strategy. Approval for US data use was given by the study coordinator 2 . Results: All patients in the Romanian cohort were Caucasian, with a mean age of 58.7 years (SD 11.6). 78% were females and the mean disease duration was 11.2 years (SD 8.3). Data was concordant with results from the previously published study. More patients from US had college education (60% vs 43.9%). Among the respondents, 93.3% Romanians were on a synthetic DMARD versus 97.7% Americans and 64.01% were currently on a biologic of choice compared to 74% patients in the US. More than half of the patients in both regions had a history of biologic DMARD use. Asked to grade (0 very good, 10 very bad ) their disease activity on the survey day, a large category of patients (37.4%, SD 14.1) marked an average state (4-6), while 19.08% (SD 11.2) were feeling poorly related to their disease. Patients were asked to define their adherence to RA treatment in the last 30 days. While the US study reported that 93% of patients were adherent 2, in our study only 62.5% of the Romanian patients reported adherence (p<0.01). A significantly lower proportion of Romanian patients were aware of T2T strategy (35 %, p 0.04). Regarding patient beliefs on their disease, statements were grouped into categories such as difficulty managing pain, medication safety, adherence, lifestyle. Most European patients would agree to change treatment to lower pain. Almost 82% stated they would accept rare adverse events in order to avoid invalidity, to confirm a better future outcome. US patients were more prone to stick to current therapy than escalade to increase clinical response. However, asked about novel therapies, Romanians were reluctant to changing treatment despite insufficient benefit, if the risk of cancer was noted. There was a high agreement that a delay in treatment would be unsatisfactory for both familial and professional chores. Conclusion: There are regional differences in knowledge and perceptions about RA treatment. Romanian patients know less on T2T algorithm. Improving awareness of the T2T strategy among RA patients may need different types of support depending on the patient's place of residence. References: [1]Smolen, J. S. et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2016 update. Ann. Rheum. Dis. 76, 960–977 (2017). [2]Owensby, J. K. et al. Patient- and Rheumatologist- Perspectives Regarding Challenges to Achieving Optimal Disease Control in Rheumatoid Arthritis. Arthritis Care Res. (Hoboken). 0–2 (2019). Disclosure of Interests: CLAUDIA COBILINSCHI Speakers bureau: novartis, Maria Danila Speakers bureau: as personally stated, Daniela Opris-Belinski Speakers bureau: as declared, Ioana Saulescu Speakers bureau: Eli-Lilly, Pfizer, Laura Groseanu Speakers bureau: novartis, eli-lilly, ucb, pfizer, sandoz, Sanziana Daia-Iliescu Speakers bureau: sandoz, Catalin Codreanu Consultant of: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Speakers bureau: Speaker and consulting fees from AbbVie, Accord Healthcare, Alfasigma, Egis, Eli Lilly, Ewopharma, Genesis, Mylan, Novartis, Pfizer, Roche, Sandoz, UCB, Razvan Ionescu Speakers bureau: as personally stated, Magda Parvu Consultant of: Speaker fee and consultant: Pfizer, Novartis, Roche, Abbvie, UCB, Eli-Lilly, Speakers bureau: Speaker fee and consultant: Pfizer, Novartis, Roche, Abbvie, UCB, Eli-Lilly, Horatiu Popoviciu Speakers bureau: as personally stated, CODRINA ANCUTA Consultant of: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly, Speakers bureau: AbbVie, Pfizer, Roche, Novartis, UCB, Ewopharma, Merck Sharpe and Dohme, and Eli Lilly, Elena Rezus: None declared, Claudia Mihailov Speakers bureau: as personally stated, Ruxandra Ionescu Consultant of: Consulting fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz, Speakers bureau: Consulting and speaker fees from Abbvie, Eli-Lilly, Novartis, Pfizer, Roche, Sandoz